EcoMusic: An Ecological Musical Robot - Andrade, Jose Lindenberg De; Araújo, Márcie Valério De; Alsina, Pablo Javier; Goncalves, Luiz M. G. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
With the increasing developments observed in Edu-cational Robotics field, many robotics projects have been created helping students and professionals in this topic to acquire knowledge and develop their work. There are several educational robotics kits already marketed worldwide, however, with only a few of them suitable for classroom use, i.e., fulfilling a substantial degree of alignment with the country's educational documents such as the Brazil's National Common Curricular Base (BNCC). In this direction and still inside Educational Robotics, the use of music is one such topic that has been little developed and that is addressed in this work. Hence, we wish to express in this work the understanding of how Music is used inside educational robotics activities and to give further directions on its possible use. Towards this goal, this work proposes an educational robotics approach named EcoMusic, created based on the BNCC skills for early childhood, elementary, and high school education. The project consists on developing the basics for having a musical robot using electronic components and recycled materials. In addition to addressing musicalization, it involves concepts of programming, electrical engineering, and mechanics, which are pillars of educational robotics. Our experiments deomsntrate the viability of the developed tools.